Innovative human resources management: key competencies expected from hospitality graduates in Ghana - Commey, Vida; Kokt, Desere; Hattingh, Johan (Goodwood Publishing, 2020)
Purpose: The study aimed to determine the key competencies required from hospitality graduates from the hospitality industry perspective. Research Methodology: The study adopted a qualitative research approach. Overall, 43 hotel managers in the Ghanaian hospitality industry were conveniently sampled. Data were collected using a structured survey questionnaire. The study used Statistical Package for Social Sciences (IBM SPSS) version 23 to analysed data collected. Results: Results from the study indicate that the “key competencies” required from hospitality graduates from the industry perspective include good inter-personal skills, innovation and ability to think of new ways of doing things, ability to maintain professional standards, customer-oriented, critical thinking ability, self-motivation, friendly and approachable, good communication skills. Limitation: The study focused only on hospitality employers in Ghana; therefore, findings from the study cannot be generalised to other hospitality employers in different country. Contribution: The study emphasises the need for hospitality educational institutions in Ghana to assess the tourism and hospitality industry's competencies to produce graduates who will fit in the job market. Keywords: Attributes, Employers, Knowledge, Skills